A comparative Study of Aptasensor Vs Immunosensor for Label-Free PSA Cancer Detection on GQDs-AuNRs Modified Screen-Printed Electrodes - Srivastava M.; Nirala N.R.; Srivastava S.K.; Prakash R. (My University, 2025)
Label-free and sensitive detection of PSA (Prostate Specific Antigen) is still a big challenge in the arena of prostate cancer diagnosis in males. We present a comparative study for label-free PSA aptasensor and PSA immunosensor for the PSA-specific monoclonal antibody, based on graphene quantum dots-gold nanorods (GQDs-AuNRs) modified screen-printed electrodes. GQDs-AuNRs composite has been synthesized and used as an electro-active material, which shows fast electron transfer and catalytic property. Aptamer or anti-PSA has immobilized onto the surface of modified screen printed electrodes. Three techniques are used simultaneously, viz. cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedence spectroscopy (EIS) to investigate the analytical performance of both PSA aptasensor and PSA immunosensor with its corresponding PSA antigen. Under optimum conditions, both sensors show comparable results with an almost same limit of detection (LOD) of 0.14 ng mL-1. The results developed with aptasensor and anti-PSA is also checked through the detection of PSA in real samples with acceptable results. Our study suggests some advantages of aptasensor in terms of better stability, simplicity and cost effectiveness. Further our present work shows enormous potential of our developed sensors for real application using voltammetric and EIS techniques simultaneous to get reliable detection of the disease. © 2018 The Author(s).